The Importance of Physical Screening in Enhancing Athlete Performance: A Literature Review of Health and Injury Prevention Aspects - Nimrot Manalu; Yikren Marito Marbun; Nikolas Marupa Turnip; Boja Nerta Sembiring (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2025)
Objectives: This literature review examines the role of physical screening in enhancing athletic performance through health optimization and injury prevention strategies. The study aims to synthesize current evidence on screening methodologies and their impact on athlete safety and performance outcomes. Methods: A comprehensive literature review was conducted using electronic databases to identify relevant studies on physical screening in athletics. Studies were selected based on predetermined criteria focusing on pre-participation screening, injury prevention, and performance enhancement methodologies. Results: The analysis revealed that comprehensive physical screening programs incorporating pre-participation medical evaluations, functional movement assessments, and advanced monitoring techniques significantly contribute to injury prevention and performance optimization. Key screening components include cardiovascular assessments, musculoskeletal evaluations, biomechanical analyses, and integrated approaches combining conventional and innovative monitoring methods. Conclusion: Physical screening serves as a fundamental component in athlete health management and performance enhancement. The integration of traditional screening methods with advanced technologies provides comprehensive athlete assessment capabilities, enabling personalized interventions for optimal performance and injury prevention.